Video surveys of sea snakes in the mesophotic zone shed light on trends in populations - Speed, Conrad W.; Wilson, Nerida G.; Somaweera, Ruchira; Udyawer, Vinay; Meekan, Mark G.; Whisson, Corey; Miller, Karen (Frontiers in Marine Science, 2022)
Declines in abundance of sea snakes have been observed on reefs throughout the Indo-Pacific, although the reasons are unknown. To date, surveys have occurred on shallow reefs, despite sea snakes occurring over a large depth range. It is not known if populations of sea snakes in deep habitats have undergone similar declines. To address this, we analysed deep-water video data from a historical hotspot of sea snake diversity, Ashmore Reef, in 2004, 2016, and 2021. We collected 288 hours of video using baited remote underwater videos and a remotely operated vehicle at depths between 13 and 112 m. We observed 80 individuals of seven species with Aipysurus laevis (n = 30), Hydrophis peronii (n = 8), and H. ocellatus (n = 6) being the most abundant. Five of the species (A. duboisii, A. apraefrontalis, H. ocellatus, H. kingii, and Emydocephalus orarius) had not been reported in shallow waters for a decade prior to our study. We found no evidence of a decline in sea snakes across years in deep-water surveys, although abundances were lower than those in early shallow-water surveys. A comparison of BRUVS data from 2004 and 2016 was consistent with the hypothesis that predation by sharks may have contributed to the loss of sea snakes in shallow habitats. Our study highlights the use of underwater video to collect information on sea snakes in the mesophotic zone and also suggests that future monitoring should include these depths in order to capture a more complete representation of habitats occupied.